Work systems framework for teaching workload model deployment at universities in South Africa - Nnadozie, R.; Chinomona, P. (South African Journal of Higher Education, 2024)
Academic workload management is a growing concern for public universities in South Africa. Over the period from 2008 to 2021, the student headcount in the higher education system has increased from approximately 800,000 to around 1,100,000 representing a 34 per cent increase. In contrast, the academic staff headcount witnessed a 28 per cent increase, emphasizing the challenges posed by the growing student population on the higher education system. However, state funding has failed to match the rate of inflation and the increase in the student headcount. Consequently, the teaching load has increased without corresponding growth in resources. This situation necessitates optimal planning and distribution of resources, particularly academic personnel. In developing the Teaching Workload Work System, Alter’s Work System Framework was adopted to evaluate the teaching workload problem by mapping its components using the concept of Key Elements in Alter’s Work Systems Framework. This article proposes a work systems framework for the management of teaching workload.